Effects of photoperiod on the melatonin cycle of Dybowski's frog (Rana dybowskii). Issue 10 (3rd October 2022) - Hu, Nan; Zhao, Xinmiao; Jin, Jiaxin; Zhao, Yingying; Wei, Hua; Li, Xiang; Li, Yingdong
ABSTRACT: There are few studies on the relationship between photoperiod and the melatonin cycle in amphibians. To elucidate the role of the photoperiodically modulated endogenous melatonin cycle in different tissues of Dybowski's frog ( Rana dybowskii ), its serum, liver, whole brain, skin, and eyeballs were collected under five photoperiods, and the daily variation in melatonin concentration was determined via high-performance liquid chromatography. Compared with the control group (12 L:12 D), melatonin concentration was increased under photoperiods 0 L:24 D and 6 L:18 D in serum, and the concentration peaked at 00:00 under photoperiod 0 L:24 D. This trend was synchronized with the peak melatonin concentration in the retinal, liver, and whole-brain tissues. After 24 h of light exposure, no significant daily variation was observed under photoperiod 24 L:0 D. Furthermore, we observed a significant peak at 04:00 in the serum under photoperiod 18 L:6 D. However, we observed the opposite trend in the circadian rhythm of the skin tissue. Our results underscore the high sensitivity of melatonin content to different photoperiods. These findings may have real-world implications in terms of furthering our understanding of circadian rhythms disruption induced by exposure to different photoperiods.